ACTIVITY AND THERMODYNAMIC PARAMETERS OF UREASE IN SOILS AMENDED WITH ORGANIC RESIDUES - & et al., Al-Ansari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
An experiment was conducted to study the thermodynamic parameters (Q10, Ea, Ha, Sa and Ga) of urease in loamy sand and silty clay soils treated with different sources of organic residues (cow residue, alfalfa leaves, wheat straw and poultry residue). Residues were mixed with soil at rate of 2%. The amended soils were incubated at 30°C for 30 days to undergo biochemical, chemical and physico-chemical reaction. Amended soils were incubated at 10, 20, 30, 40, 50, 60, 70 and 80°C. Urease activity was assayed and thermodynamic parameters were calculated. Results indicated that urease activity of amended soil was higher than that of control soils at various temperatures of incubation. Urease activity increased by increasing temperature of incubation from 10 to 40°C. Q10, Ea, Ha, and Sa values of silty clay soil were in the order of : poultry manure > cow manure > alfalfa residue > wheat residue > control soil. However, in loamy sand soil the order was cow manure > alfalfa residue > wheat residue > control > poultry manure. Order of Ga was control > wheat residue > alfafa residue > cow manure > poultry manure at both soils. Except at poultry manure, all thermodynamic parameters values were higher in loamy sand soil as compared with their values in silty clay soil.